Ethnochoreology at the Faculty of Music in Belgrade - from the folklore paradigm to the discourse of institutional and nationally specific disciplinary orientation in the time of (post)tradition - Rakočević Selena; Ranisavljević Zdravko (Glasnik Etnografskog Instituta SANU)
The founder of ethnochoreology as an academic scholarly discipline in Serbia is ethnologist and ethnochoreologist Dr. Olivera Vasić, whos research and educational approach continued the activities of the Ljubica and Danica Janković. The methodological basis of this scholarly paradigm is grounded on the folkloristically-based idea of collecting and preserving ethnically distinctive traditional dances marked with the expression “narodna igra“ (literally: folk game) in order to construct and maintain nationally distincitive Serbian culture, first by reconstructing old village dances within the field research processes, and then by notation of kinetic and musical components of particular dances and publication of dance ethnographies of individual geographical areas. Academic ethnochoreological education at the Faculty of Music began on the basis of this approach in 1990. After 2000, through developement of the teaching staff consisted of young scholars who started to teach ethnochoreological courses and their indirect education within the international academic and scholarly framework, it began to transform. The key theoretical and methodological turn can be considered the conceptualization of the term “traditional dance“ (see: Rakočević 2011). The use of this expression implies differentiation of dance components (kinetics and music), making sense in the processes of synthetic perception of textual and contextual levels of dance realizations, and at the same time marks the diffuse expansion of folkloristic paradigm of ethnochoreological research from rural “folk games“ from the past to various forms of dance, interpretatively positioned within the ambiguous field of “traditional“ cultural expression. The unique theoretical concepts that arise from this institutionally and nationally specific ethnochoreological discourse have a specific potential within applied scholarly activities, which gives this discipline a distinctive meaning in the era of safeguarding intangible cultural heritage. The paper diachronically examines and theoretically interprets the practice of ethnochoreological education at the Faculty of Music in Belgrade, with a special focus on the processes of transforming institutionally and nationally specific scholarly paradigms.